2018
DOI: 10.1111/jphs.12280
|View full text |Cite
|
Sign up to set email alerts
|

Primary care physician perspectives on barriers and facilitators to self-management of type 2 diabetes

Abstract: Objectives To assess physician perspectives on perceived barriers and facilitators to type 2 diabetes self‐management (DSM) in a primary care setting. Methods The study utilized survey methodology to measure perspectives of primary care physicians on DSM and the challenges they face in managing patients with poor glycaemic stability. Demographic and practice site‐related information of the physicians were also collected. Key findings Of the 21 physicians who responded (53.8% response rate), 71.2% were aged 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Also, autonomous motivation was positively associated with professionals' beliefs regarding parental self‐management. In the interviews, professionals expressed several work‐related factors limiting their autonomy to empower parents for self‐management, such as lack of time, scheduling problems, austerity and general lack of self‐management policy in the institute, echoing earlier findings (Coyne, 2015 ; Khairnar et al, 2019 ). General work issues encountered by professionals interfered with their motivation to change their behaviours or led them to refrain from investing extra time and energy, like, for instance, taking up contact with parents outside of the scheduled treatment sessions.…”
Section: Discussionmentioning
confidence: 52%
“…Also, autonomous motivation was positively associated with professionals' beliefs regarding parental self‐management. In the interviews, professionals expressed several work‐related factors limiting their autonomy to empower parents for self‐management, such as lack of time, scheduling problems, austerity and general lack of self‐management policy in the institute, echoing earlier findings (Coyne, 2015 ; Khairnar et al, 2019 ). General work issues encountered by professionals interfered with their motivation to change their behaviours or led them to refrain from investing extra time and energy, like, for instance, taking up contact with parents outside of the scheduled treatment sessions.…”
Section: Discussionmentioning
confidence: 52%
“…A detailed summary of evidence is provided in the Supporting information (Appendix S1). The records 3,14,45,46 offering the richest data extraction were also rated highly for quality (Appendix S2).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Two key clinician-related points were cited as significant or very significant: limited time for education and lack of access to education services, partly as a result of to poor financial reimbursement to the provider and an absence of staff education. Similarly, Khairnar et al 46 found lack of time for patient follow-up to be extremely or very important to primary care physicians. In that study, patient-related factors were identified as reasons: patient nonadherence or indifference to dietary advice.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Khairnar et al (2018) asserts that the inevitable clinical skill of the physician is to provide information to the patient at an individual level, clearly and together with the patient to consider treatment options. The system striving for the improvement of care for chronically ill patients must be motivated and ready to change in terms of its overall organization.…”
Section: Discussionmentioning
confidence: 99%